KONTROVERSI PERKAWINAN BEDA AGAMA DI INDONESIA - Sri Wahyuni (Jurnal Hukum Islam, 2010)
Implementation of interfaith marriage after the enactment of the Marriage Act No. 1/1974 is relatively difficult. The Act itself causes polemic in the understanding and implementation of interfaith marriage to appear. This paper tries to discuss different ideas controversy deals with interfaith marriage, the concept of marriage validity and legality under the Marriage Act, and deep discussion about interfaith marriage before and after the enactment of the Marriage Act.